(untitled) (Global Journal of Human-Social Science, 2012)
This paper presents an understanding of the contribution made by tourism towards poverty eradication in selected rural areas in Selangor Malaysia Rural homestay programmes as a viable tourism product in Malaysia is comparatively small in scale and still remains a slow growth market even though various incentives are being offered to the operators by the government to develop this market Poverty is the root cause of many social ills such as illiteracy crime drug abuse and high rate of divorce Although tourism has been adopted as a strategy for poverty eradication in Selangor it has not been fully exploited by the rural community and those that have are finding it difficult to sustain This research is undertaken with the aim of putting together a model or identifying variables that will ensure the economic sustainability of rural homestay programmes in Selangor Malaysia Through factor analysis the variables of the communities involvement in tourism activities were identified